Digital Learning and Teaching in Chemistry 2023
DOI: 10.1039/9781839167942-00376
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Back Learning Communities in the 21st Century

Abstract: The COVID-19 pandemic has underlined the issue of educational inequality. There is evidence that students from low-income families and underrepresented minorities struggled to adjust to the digital environment for various reasons, exacerbating challenges that other students face in a digital classroom. To alleviate these inequalities, we propose that educators deliberately build online student communities using social or digital media platforms. However, establishing such communities prove challenging due to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…4 With in-person teaching limited, the instructors established a vibrant Discord channel as an asynchronous learning community for students to connect, learn, and engage outside of class, combatting isolation and fostering a sense of belonging. 5 This, along with growing evidence of the benefits of peer-to-peer learning techniques, 6 underscores the potential of technology to enrich the learning process beyond the confines of traditional methods.…”
Section: Learning Strategiesmentioning
confidence: 99%
“…4 With in-person teaching limited, the instructors established a vibrant Discord channel as an asynchronous learning community for students to connect, learn, and engage outside of class, combatting isolation and fostering a sense of belonging. 5 This, along with growing evidence of the benefits of peer-to-peer learning techniques, 6 underscores the potential of technology to enrich the learning process beyond the confines of traditional methods.…”
Section: Learning Strategiesmentioning
confidence: 99%
“…Escape rooms have been a popular way of conducting educational activities in class, employed by educators from many fields, including programming, communication skills, and team-building. Compared to other gamification approaches such as Leader boards and Quest, it has been found that the escape room format helps to enhance learning engagement, promote communication between students, as well as develop critical thinking. , …”
Section: Using Gather As An Online Escape Roommentioning
confidence: 99%